Depletion of myeloid-derived suppressor cells alleviates kidney damage in murine membranous nephropathy - Li, Huimin; Wei, Anhui; Ma, Zhanchuan; Yang, Li; Xiao, Xia; Liu, Chang; Teng, Chunyan (Frontiers in Immunology, 2025)
Based on previous studies on myeloid-derived suppressor cells (MDSCs) and T helper 17 (Th17) cells in patients with primary membranous nephropathy (PMN), we successfully established a murine PMN model to investigate the relationship between MDSCs, T cells, and disease progression. Our study demonstrated that MDSCs and their subclasses, as well as Th17 and T helper 2 (Th2) immune responses, were enhanced. In contrast, the proportion of T helper 1 (Th1) and regulatory T (Treg) cells decreased with PMN progression. Depletion of MDSCs with gemcitabine reduced the proportion of Th17 and Th2 cells and the expression of related transcription factors. Conversely, the proportions of Th1 and Treg cells increased in the circulation, spleen, lymph nodes, and kidneys, alleviating the clinical manifestations and pathological damage to the renal tissue in PMN model mice. These findings suggest that MDSCs, along with Th17 and Th2 responses, play critical roles in PMN progression. MDSCs may contribute to disease progression by regulating the differentiation and immune response of T-cell subclasses. The data provide new insights into the etiology, pathogenesis, clinical diagnosis, and treatment of membranous nephropathy.